Direct detection of toxigenic Bacillus cereus in dietary complement for children and cassava starch (2014)
Bacillus cereus is a food contaminant anda known human pathogen that can causeemetic and diarrheal syndromes. In this studywe evaluated the presence of toxigenic B.cereus by multiplex PCR directly in dietarycomplement for children and cassava starchsamples collected on Medellin, Colombia.Of 75 dietary complement for childrensamples evaluated, 70.7% were contaminatedwith toxigenic B. cereus and four differenttoxigenic consortia were detected: I: nheA,hblC, cytK (9.8%), II: nheA, hblC (2%),III: hblC, cytK (41.2%), IV: hblC (47%).Of 75 cassava starch samples, 44% werecontaminated with toxigenic B. cereus andfour different toxigenic consortia weredetermined: I: nheA, hblC, cytK (48.5%),II: nheA, hblC, cytK, cesB (3%), III: hblC,cytK (30.3%), IV: hblC (18.2%). In general,in dietary complement for children onlyenterotoxigenic consortia were detectedwhile in cassava starch the enterotoxigenicconsortia predominated over the emetic.Multiplex PCR was useful to detect toxigenicB. cereus contamination allowing directand simultaneous detection of all toxingenes in foods. This study is the first inColombia to evaluate toxigenic B. cereus,providing information of importance formicrobiological risk evaluation in driedfoods.